Chemically Engineered Nanoparticle–Protein Interface for Real‐Time Cellular Oxidative Stress Monitoring. Issue 28 (13th June 2016) - Jiang, Ying; Wang, Ming; Hardie, Joseph; Tonga, Gulen Yesilbag; Ray, Moumita; Xu, Qiaobing; Rotello, Vincent M.
Abstract : A co‐engineered nanoparticle/protein peroxide detector is created . This system features a gold nanoparticle functionalized with a galactose headgroup (AuNP‐Gal) that reacts covalently with a boronate‐modified green fluorescent protein (PB‐GFP). Boronate acid‐saccharide complexation between PB‐GFP and AuNP‐Gal affords a highly stable assembly. This complex is disrupted by peroxide, allowing quantitative and selective monitoring of hydrogen peroxide production in real time.